Biofortification of Pulses: Strategies and Challenges - Singh, Ummed; Praharaj, C. S.; Singh, S. S.; Bohra, Abhishek; Shivay, Y. S. (International Journal of Economic Plants, 2015)
Pulses are the prime source of dietary proteins of the vegetarian people inhabiting mostly in the developing countries. In general, pulses provides around 18-28% protein and one third of all dietary protein nitrogen. Besides dietary proteins, these also offer many minerals required essentially by the human beings. The production of pulses in the country over the years especially during the last decade has tremendously improved as a record pulses production of 18.34 million tonnes was realized during 2012-13. For 2013-14, the 4thadvance estimates of DAC have predicted the production to touch 19.27 million tonnes-a significant milestone in the pulses scenario. Biofortification, the process of integrating nutrients into food crops, provides a sustainable and economic way of increasing the density of minerals or micronutrients in important staple crops. This approach will help to control the volume of malnourished people worldwide. Moreover, biofortification presents an easily accessible means especially concerned to the malnourished population in rural areas who normally have either no or very poor accessibility to market places. Therefore, biofortification strategy aims to incorporate the nutrient accumulation and related plant attributes in those commercially accepted and superior cultivars that are already in food chain due to their good agronomic performances, primarily the seed yield.